Análisis de la Evolución de las Tasas de Interés en el Ecuador, período 2000-2017 - Zambrano Jiménez, Maritza Maribell (2020)
The objective of this research is to analyze the evolution of interest rates in Ecuador, period 2000-2017. The compilation of the information was based on books, bulletins and reports from the Central Bank of Ecuador and ECLAC, which achieved the fulfillment of the objectives. For the development of the work, a comparative description of interest rates in Ecuador was made. Likewise, the main factors affecting these were determined, within the indicated period; which is divided into two time frames; the first from the year two thousand to two thousand seven, a period in which the dollarization of the Ecuadorian economy begins, while the second is from two thousand eight to two thousand seventeen, distinguished by the implementation of the president's public policies Rafael Correa. Likewise, the five-year interest rate projection was carried out through a simple linear regression for active rates and weighted moving averages for deposit rates. Finally, conclusions and recommendations of the work are specified. Thus, Thus detailing that, the main factors that affected interest rates in Ecuador for the 1993-1999 period were the depreciation of the currency, high inflation and the 1% tax on Capital Circulation, causing high interest rates on loans, deposit freezes and collapses of various financial institutions. As well as impact on prices and decrease in financial profitability. Likewise, in the period 2000 - 2007, the implementation of dollarization and the return of reserve funds to IESS affiliates for US $ 454 million, which caused interest rates to decrease, stand out. Finally, in the 2008-2017 period, interest rates were affected by the implementation of several regulatory changes that led to reforms in interest rates, change of instructions, implementation of new credit segments, interest rate reduction, injection of capital to the national financial system, strengthening of the economic sector and recovery of the demand for credit and deposits.